Identifying vulnerable population groups: On-time infant vaccination coverage in Australia - Moore, Hannah; Fathima, Parveen; Gidding, Heather; de Klerk, Nicholas; Liu, Bette; Sheppeard, Vicky (International Journal of Population Data Science, 2018)
Introduction Immunisation coverage is a good measure of immunisation program effectiveness. Coverage of the 3-dose infant schedule in Australia assessed at age 12 months is >90%. Timeliness is an important goal for population immunity, but on-time coverage of the 2-4-6 month schedule and coverage in specific populations is rarely reported. Objectives and Approach We conducted a retrospective population-based cohort study of 1.9 million Australian births, 1996-2012 (approximately 42% of Australia’s population). Individual data from state-held birth and perinatal records were combined with Commonwealth-held immunisation and death records, through probabilistic linkage. We assessed on-time coverage across 13 demographic and perinatal characteristics of diphtheria-tetanus-pertussis vaccines (DTP) defined as vaccination 14 days prior to the scheduled due date, to 30 days afterwards. Results On-time DTP vaccination coverage in non-Aboriginal infants was 88.1% for the 2-month dose, 82.0% for 4-month dose, and 76.7% for 6-month dose; 3-dose coverage was 91.3% when assessed at 12 months. On-time DTP coverage for Aboriginal infants was 77.0%, 66.5%, and 61.0%; 3-dose coverage at 12 months was 79.3%. Appreciable differences in on-time coverage were observed across population subgroups. On-time coverage in non-Aboriginal infants born to mothers with ≥3 previous pregnancies was 62.5% for the 6-month dose (47.9% for Aboriginal infants); up to 23.5% lower than for first-borns. Infants born to mothers who smoked during pregnancy had coverage 8.7-10.3% lower than infants born to non-smoking mothers for the 4- and 6-month dose. A linear relationship was apparent with increasing socio-economic disadvantage and decreasing on-time coverage. Conclusion/Implications On-time vaccination coverage of the 2-4-6 month schedule is only 50-60% across specific population subgroups representing a significant avoidable public health risk. Australian Aboriginal infants, multiparous mothers, and those who are socio-economically disadvantaged are key groups most likely to benefit from targeted programs addressing vaccine timeliness.